Mineralogical, Geochemical, and Raman Spectral Characteristics of Amphibole Mineral Types in Amphibolite from Southern Sanandaj-Sirjan Metamorphic Belt (Iran) - Moeinzadeh, Hesam; Rahimisadegh, Hadiseh; Moazzen, Mohsen; Nakashima, Kazu (Indonesian Journal on Geoscience, 2021)
DOI: 10.17014/ijog.8.1.59-72The current study is related to amphiboles in amphibolite rocks in the northwest of Golgohar Iron Mine located in the southern part of Sanandaj-Sirjan metamorphic zone.Petrography observations indicate that the studied rocks are of ortho-amphibolite type, formed from metamorphism of igneous rocks. The analysis of amphibole crystals in amphibolites of the region was done by petrography, electron microprobe, and Raman spectroscopy. Raman spectral pattern of the studied minerals was discussed in comparison to mineral type and chemistry characteristics. Based on mineral chemistry studies, it was discovered that all amphiboles in the studied rocks are calcic with (Ca+Na)Bâ‰¥1.34 and SiIV between 6.27 and 6.76 atoms per formula unit. Based on their enrichment in the elements Al and Fe3+, their composition varies from tschermakite to magnesio-hornblende. Raman spectral peak pattern for amphiboles and terrestrial tremolite does not have significant discriminable differences. However, Raman peak patterns of tremolite have clearly different features versus tschermakite. According to the general formula of amphiboles [A0-1B2C5T8O22(OH, F, Cl)2], the Raman spectrum variability of the tschermakite and tremolite can be due to the position of A site, Al incorporation into M1 + M2 + M3 sites and into the T site.